Efektifitas Instrumen Penilaian Volume Kubus Dan Balok Dalam Pembelajaran Matematika Sd Berbasis Macromedia Flash Di Kelas V Sd Bangetayu Wetan 02 - Aziz, Khatmirul; Nugroho, Heru Siddik (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
This study aims to determine the effectiveness of the assessment instrument for the volume of cubesand rectangular prisms in elementary school mathematics learning using Macromedia Flash in the fifth-grade class of SD Bangetayu Wetan 02. The research adopts a quantitative or experimental approach withthe Intact-Group Comparison design, where the researcher divides the class into two groups: anexperimental class and a control class. These two classes are then compared using different treatments. Thesampling method used is non-probability random sampling, taken from the population of SD BangetayuWetan 02, with the sample being the fifth-grade class. The data validation techniques employed includevalidity and reliability tests to evaluate the instrument, while content validity is assessed by expert validators.For data analysis, the researcher applies normality tests, homogeneity tests, and T-tests to examine theeffectiveness of the tested instrument and to identify differences in outcomes between the experimental andcontrol classes. The findings reveal that the assessment instrument for the volume of cubes and rectangularprisms in elementary school mathematics learning using Macromedia Flash is effective. The results showa Levene’s Test for Equality of Variances significance value of 0.00 < 0.05, indicating a significant differencein the average evaluation results between the experimental and control classes. The control class achieved ahigher average score of 75.96, while the experimental class obtained an average score of 52.57.Keywords: Assessment Instrument, Mathematics, Macromedia Flash